Nigeria pre-school environmental characteristics: a survey study (2008)
This study evaluated the environmental characteristics of preschool settings in Nigeria. The factors looked into include physical, human ad material environments of the pre-school settings, teaching learning processes, organization of activities, school location, as well as availability and use of teaching learning materials. The sample size consisted of 72 preschool settings; 2859pupils aged 4 - 5 years. Schools were selected through stratified random sampling to en sure adequate representation of private, public, urban and rural schools. Three valid and reliable school observational instruments were used to obtain evidence on the variables of concern. Data collection involved the use of observational technique (structured instrument and unstructured, video camera) to generate evidence in 216 lessons observed in 72 schools. Data Analyses involved the use of frequencies, percentages and graphical illustrations. The result revealed that most preschool environments are characterized by inadequate provision of materials, decay in school building structures, teachers not trained to teach at this level, use of lecture methods instead of play as well as teacher-whole class interaction denominated by the teachers during instructional delivery.